2018
DOI: 10.3390/cancers10110444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Regulating Organ-Specific Metastases in Epithelial Ovarian Carcinoma

Abstract: Epithelial ovarian carcinoma is the most predominant type of ovarian carcinoma, the deadliest gynecologic malignancy. It is typically diagnosed late when the cancer has already metastasized. Transcoelomic metastasis is the most predominant mechanism of dissemination from epithelial ovarian carcinoma, although both hematogenously and lymphogenously spread metastases also occur. In this review, we describe molecular mechanisms known to regulate organ-specific metastasis from epithelial ovarian carcinoma. We begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 119 publications
0
48
0
Order By: Relevance
“…Metastases in HGSOC occur through several distinct routes, which include, transcoelomic, hematogenous and lymphogenous spread [89]. The spread of OC occurs primarily through transcoelomic route, which involves metastasis in the peritoneal cavity and the surrounding peritoneal organs [90,91].…”
Section: Metastases and Tumour Microenvironment In Ocmentioning
confidence: 99%
“…Metastases in HGSOC occur through several distinct routes, which include, transcoelomic, hematogenous and lymphogenous spread [89]. The spread of OC occurs primarily through transcoelomic route, which involves metastasis in the peritoneal cavity and the surrounding peritoneal organs [90,91].…”
Section: Metastases and Tumour Microenvironment In Ocmentioning
confidence: 99%
“…Previous studies have shown that poor differentiation and lymph node involvement are risk factors for distant metastasis 3 .We found that liver metastases, brain metastases and bone metastases are risk factors for lung metastases. If distant metastasis occurs in other parts, it means that cancer cells have spread 18 ,and the possibility of lung metastases will be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian tumors do not show typical invasion features seen in other tumor types 63 . Indeed peritoneal metastases via transcoelomic dissemination appear to be a characteristic of HGSOCs 55,64 , where tumor cells detach from the primary tumor, using the ascitic fluid as a carrier to reach mesothelial cells that line the peritoneal cavity 56,65 .…”
Section: Discussionmentioning
confidence: 99%
“…EOCs undergo a particular mode of motility, where tumor cell invade the peritoneal cavity through a process called tumor dissemination 55 . Indeed tumor cells detach from the primary tumor site, adhere and go through mesothelial cells that enclose peritoneal organs 56 .…”
Section: Low Cni Ovarian Cancer Cells Cause More Efficient Mesotheliamentioning
confidence: 99%